Skill-Biased Technological Change, Unemployment, and Brain Drain. Issue 2 (1st April 2014) - Fadinger, Harald; Mayr, Karin
Abstract: We develop a model of directed technology adoption, frictional unemployment, and migration to examine the effects of a change in skill endowments on the wages, employment rates, and emigration rates of skilled and unskilled workers. We find that, depending on the elasticity of substitution between skilled and unskilled workers and the elasticity of the matching function, an increase in the skill ratio can reduce both the relative unemployment rate and the relative emigration rate (brain drain) of skilled workers. We provide numerical simulations to support our findings and show that the effects are empirically relevant and potentially sizable.